Factors influencing job satisfaction among construction site artisans in Northern Malaysia - Ahmed Mohammed Kamaruddeen,; Adibah Hani Hamdan,; Wahida Wahi, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The satisfaction of construction site workers is very important in ensuring the success of any construction project because of its impact on their commitment and site productivity. This paper aims to determine the factors influencing job satisfaction and the overall job satisfaction among the construction site Artisans across selected construction sites in Kedah, Malaysia. Using simple random sampling technique, a survey was conducted by distributing copies of questionnaire to 30 experienced construction site artisans in order to obtain the required data. SPSS was used to analyze data. Workplace environment and facilities, personal factor and supervision showed significant relationship with job satisfaction. It was also found that the satisfaction level among the artisans was high. The study concludes that job satisfaction of artisans is an important issue that should be given much attention in construction sites.